PHILOSOPHY OF CRIMINAL LAW an introduction. - Cowley, Christopher; Padfield, Nicola ([S.l.] : ROUTLEDGE, 2023)
The Philosophy of Criminal Law: An Introduction explores the central concepts of criminal law, such as intention, complicity and duress, and how they work, both within criminal law practice and in our everyday lives, from legal and philosophical perspectives. At the heart of the book is the central philosophical concept of responsibility: what does it mean to be responsible for an act, to hold someone responsible for an act, or to give an excuse in order to avoid responsibility for an act? Offering talking points to enrich an ongoing conversation, this unique textbook addresses all of these questions in an accessible way for law and non-law students alike. Real cases are examined in detail and a critical approach to the criminal law is adopted throughout. The focus will be mainly on the criminal law of England and Wales, with occasional cases from other jurisdictions, and occasional examples from other areas of law. This text will be ideal reading for advanced undergraduate and graduate students of law, philosophy and criminology, as well as political science and sociology.
Keywords: Criminal law -- Philosophy; PHILOSOPHY / General; LAW / Criminal Law / General; LAW / Jurisprudence